1973
DOI: 10.2172/4486196
|View full text |Cite
|
Sign up to set email alerts
|

Forced-convection heat-transfer measurements with a molten fluoride salt mixture flowing in a smooth tube

Abstract: ·This report was prepared as an account of work sponso~ed by the United States Government. Neither the Un.'t~d States nor the United States Atomic Energy Co':"m•ss•on, nor any of their employees, nor any of theu contractors, sub~ontractors, or their employees makes _anr. warranty, express or implied, or Bssumes an ' tlegal hab1hty or responsibility for the accuracy cor: pleteness or usefulness of any information app~ratus ~ product or. pr?cess disclosed, or: represents 'that its us~ would not mfnnge privately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 2 publications
1
15
0
1
Order By: Relevance
“…It was also found that "the overall heat transfer coefficient of the MSRE heat exchanger did not change during 22,000 h of salt circulation and 13,000 equivalent full-power hours of operation, thus indicating no buildup of scale and no evidence of gas filming" [49]. Detailed forcedconvection heat-transfer measurements confirmed this same behavior in out-of-pile tests with the MSBR fuel salt composition [50].…”
Section: Thermal Conductivitymentioning
confidence: 85%
“…It was also found that "the overall heat transfer coefficient of the MSRE heat exchanger did not change during 22,000 h of salt circulation and 13,000 equivalent full-power hours of operation, thus indicating no buildup of scale and no evidence of gas filming" [49]. Detailed forcedconvection heat-transfer measurements confirmed this same behavior in out-of-pile tests with the MSBR fuel salt composition [50].…”
Section: Thermal Conductivitymentioning
confidence: 85%
“…Several earlier studies were performed to understand molten salt heat transfer in advanced reactors applications [3][4][5][6][7][8][9][10]. Hoffman [3] studied turbulent heat transfer for molten NaOH for Re~ 6000-12000 and concluded that heat .…”
Section: Introductionmentioning
confidence: 99%
“…Hoffman and Cohen [7] studied molten NaNO 2 -NaNO 3 -KNO 3 (HTS) system for heat transfer behavior for Re ~ 4850-24710 and heat flux up to 614 kW/m 2 , and reported good agreement between their data and the Dittus-Boelter equation. Cooke and Cox [8] studied heat transfer for LiF-BeF 2 -ThF 4 -UF 4 within Re ~ 400-30600. Silverman et al [9] studied LiF-BeF 2 -ThF 4 -UF 4 and NaBF 4 -NaF (both reactor fuel salts) in the range of Re~ 1540-45000 and up to heat flux of 630 kW/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Paddle dryer is then given a more general name -paddle heat exchanger as its application is beyond the scope of drying. Although molten salt flow and heat transfer in simple ducts and some applications (e.g., solar thermal power systems) have been investigated extensively [10][11][12][13][14][15][16][17][18][19][20], no research on molten salt paddle heat exchangers is presented.…”
Section: Introductionmentioning
confidence: 99%